Once-yearly zoledronic acid in hip fracture prevention - Oddom Demontiero (Dove Medical Press, 2009)
Oddom Demontiero, Gustavo DuqueAging Bone Research Program, Nepean Clinical School, University of Sydney, Penrith, NSW, Australia; Department of Geriatric Medicine, Nepean Hospital, Penrith, NSW, AustraliaAbstract: Osteoporosis is an escalating global problem. Hip fractures, the most catastrophic complication of osteoporosis, continue to cause significant mortality and morbidity despite increasing availability of effective preventative agents. Among these agents, oral bisphosphonates have been the first choice for the treatment and prevention of osteoporotic fractures. However, the use of oral bisphosphonates, especially in the older population, has been limited by their side effects and method of administration thus compromising their persistent use. The resultant low adherence by patients has undermined their full potential and has been associated with an increase in the incidence of fragility fractures. Recently, annual intravenous zoledronic acid (ZOL) has been approved for osteoporosis. Randomized controlled trials have demonstrated ZOL to be safe, have good tolerability and produce significant effect on bone mass and microarchitecture. Adherence has also been shown to be better with ZOL. Furthermore two large trials firmly demonstrated significant anti-osteoporotic effect (-59% relative risk reduction of hip fractures) and mortality benefit (28% reduction in mortality) of ZOL in older persons with recent hip fractures. In this review, we report the current evidence on the use of ZOL for the prevention of hip fractures in the elderly. We also report the pharmacological characteristics and the advantages and disadvantages of ZOL in this particular group.Keywords: osteoporosis, zoledronic acid, hip fracture, elderly